2016
DOI: 10.21273/hortsci.51.5.580
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Winter Overseeded and Colorant-treated ‘Tifway’ Bermudagrass Receiving Weekly Irrigation and Simulated Traffic

Abstract: Municipal water restrictions across the southern and southwestern United States have created additional challenges for maintaining safe playing surfaces on recreational turf facilities. In recent years, many cities within these regions have begun to impose irrigation restrictions during winter months. Although winter overseeding has been regularly practiced in these areas, interest and use of colorants as an alternative to overseeding has grown due to decreasing water availability and budget concerns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Winter golf cart traffic did not have a detrimental effect on nontreated buffalograss survival and spring recovery in our study (Table 1 and Table 2), which suggests that it is safe for golf courses to allow low to moderate levels of cart use during winter dormancy. These results are in agreement with past traffic research on other dormant warm‐season turf (Hargey et al., 2016). The results also demonstrated that using turf colorants to provide winter GC during buffalograss dormancy may be a better option than overseeding buffalograss in the transition zone because of the negative impact overseeding had on the spring recovery of buffalograss in both years.…”
Section: Winter Color and Spring Recovery Of Buffalograsssupporting
confidence: 93%
See 1 more Smart Citation
“…Winter golf cart traffic did not have a detrimental effect on nontreated buffalograss survival and spring recovery in our study (Table 1 and Table 2), which suggests that it is safe for golf courses to allow low to moderate levels of cart use during winter dormancy. These results are in agreement with past traffic research on other dormant warm‐season turf (Hargey et al., 2016). The results also demonstrated that using turf colorants to provide winter GC during buffalograss dormancy may be a better option than overseeding buffalograss in the transition zone because of the negative impact overseeding had on the spring recovery of buffalograss in both years.…”
Section: Winter Color and Spring Recovery Of Buffalograsssupporting
confidence: 93%
“…Overseeded perennial ryegrass was a top‐peforming treatment during both years (Table 1 and Table 2). However, the spring transition and recovery back to warm‐season turf can be challenging (Fontanier & Steinke, 2017; Hargey, Wherley, Reynolds, White, & Parker, 2016). This was also observed in our study as a result of the slow growth rate of buffalograss in combination with competition from perennial ryegrass prior to the flazasulfuron application.…”
Section: Winter Color and Spring Recovery Of Buffalograssmentioning
confidence: 99%
“…They concluded that the lawn presented color permanence for up to 197 days in the autumn/winter, but with significant loss in color at approximately 60 days. Hargey et al (2016) affirm that it is necessary to increase the number of applications to maintain the color during the winter months, which is dependent on several factors, including cultivated species and conditions of application (Figures 4 to 6). Figure 4.…”
Section: Resultsmentioning
confidence: 96%
“…Over the last decade, the practice of using colorants has increased in popularity, which according to Hargey et al (2016), may be related to water conservation efforts, as well as the reduced operating costs when compared to the cost of winter overseeding (a practice widely used on golf courses and football fields in the winter). In Brazil, bermudagrass (Cynodon spp.)…”
Section: Introductionmentioning
confidence: 99%
“…also have been developed in recent years. These annual ryegrasses facilitate easier spring transition compared with perennial ryegrass and possess finer texture and improved color compared with previous annual ryegrass cultivars (Hargey et al, 2016). Performance and quality of recent cultivars of annual ryegrass have been compared with diploid perennial ryegrass cultivars, and the results showed that transition of turf-type annual ryegrasses occurred %1 month earlier that diploid perennial ryegrass (Fontanier and Steinke, 2017;Nelson et al, 2005).…”
mentioning
confidence: 99%